(9y-3)(y-5)=0

Simple and best practice solution for (9y-3)(y-5)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (9y-3)(y-5)=0 equation:



(9y-3)(y-5)=0
We multiply parentheses ..
(+9y^2-45y-3y+15)=0
We get rid of parentheses
9y^2-45y-3y+15=0
We add all the numbers together, and all the variables
9y^2-48y+15=0
a = 9; b = -48; c = +15;
Δ = b2-4ac
Δ = -482-4·9·15
Δ = 1764
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$y_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$y_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

$\sqrt{\Delta}=\sqrt{1764}=42$
$y_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-48)-42}{2*9}=\frac{6}{18} =1/3 $
$y_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-48)+42}{2*9}=\frac{90}{18} =5 $

See similar equations:

| 2/n+6=18 | | 12-2x=-44 | | -4=-2n-1n-1 | | x/6-9=6 | | -7=0n-5+2n | | 12p-8p-2p=16 | | x/6-9=9 | | (3x-5)(×)=150 | | 3x+11=-5x-5 | | (3x-5)(×)=159 | | 4+32x=0 | | 6-3(x+5)+10x=10x-(7x-10)+8 | | -5+x=7x+55 | | 13s+4s+2s-9s-8=12 | | 2n/9=-14 | | 4(5n-6)-1=85 | | 0x-1+x=-3 | | a-a+2a=14 | | X+5=5x+29 | | 145+5b=200 | | 6=-2p+18 | | 5(1x-5)=-15 | | 7w-3w-3w-1=19 | | 8x+3+4x=8x+15 | | 0n-1+n=-3 | | y+9=-10y+51 | | 2+3n+2n=17 | | 2x-4+3x+2=4x+8 | | 10c-6c-c+3c-1=15 | | -22=2-2n-4n | | 90=37,8/x | | 4x-3=-15+7x |

Equations solver categories